Pump-Priming Payments for Sustainable Water Services in Rural Africa. (October 2015) - Koehler, Johanna; Thomson, Patrick; Hope, Robert
Highlights: Theory on rural water services is advanced through a "club good" framework. Community handpump institutional design varies by pump density, demand, and service. Dramatic advances in service reliability improve community payment behavior. Water service monitoring innovations inform a professional maintenance model. An output-based payment framework is outlined as a scalable and replicable model. Summary: Locally managed handpumps provide water services to around 200 million people in rural Africa. Handpump failures often result in extended service disruption leading to high but avoidable financial, health, and development costs. Using unique observational data from monitoring handpump usage in rural Kenya, we evaluate how dramatic improvements in maintenance services influence payment preferences across institutional, operational, and geographic factors. Public goods theory is applied to examine new institutional forms of handpump management. Results reveal steps to enhance rural water supply sustainability by pooling maintenance and financial risks at scale supported by advances in monitoring and payment technologies.